Bioethanol Technologies - Inambao, Freddie (IntechOpen, 2021)
Bioethanol Technologies explores the conceptual and methodological approaches for understanding bioethanol technologies and future perspectives. The book comprehensively covers the global scenario of ethanol production from both food and non-food crops and other sources. This book is a useful resource for those involved with biofuels in general and bioethanol in particular, including energy engineers, researchers, consultants, analysts, policy makers, and professionals in the industry supply chain. This book: • Reviews the most significant research findings in both ethanol production and utilization; • Presents technological interventions in ethanol production, from plant biomass to food crops; • Offers a foresight analysis on the perspectives of bioethanol as a global commodity; • Presents a complete overview of the main challenges that bioenergy will have to overcome in order to play a key role in future energy systems; • Presents necessary Occupational Health and Safety (OH&S) assessments.